Using next-generation sequencing for characterising HLA-DRB1 and DQB1 loci in a cohort of Colombian women (2019)
The Colombian population is characterised by a high genetic diversity, secondary to the ethnic mixture arising from colonisation. Unfortunately, few reports are available regarding HLA-DRB1 and DQB1 diversity in Colombia to date. HLA-DRB1 and DQB1 diversity was identified in this study using next-generating sequencing (NGS) on a cohort of Colombian women. Cervical samples taken from 276 women were used for typing DRB1 and DQB1 loci by Illumina MiSeq. Allele and haplotype frequencies were calculated using an expectation-maximisation algorithm. Hardy-Weinberg Equilibrium and linkage disequilibrium (LD) between loci were evaluated. Forty-seven DRB1 alleles and 14 DQB1 alleles were identified. DRB1*04:07:01G and DQB1*03:02:01G alleles occurred most frequently in the target population. Significant LD was found in 44 out of the 144 identified haplotypes, within which DRB1*04:07:01G-DQB1*03:02:01G occurred most frequently (6.56%). The alleles and haplotypes found with NGS agreed with that found in previous reports involving lower resolution for the Colombian population, and greater genetic variability was found, especially concerning DRB1. Comparing allele and haplotype frequency distribution in the target population to that of other populations denoted HLA system intra- and inter-population diversity. © 2019 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd